Time-dependent morphological alterations and viability of cultured human trabecular cells after exposure to Trypan blue - Tsaousis, Konstantinos; Kopsachilis, Nikolaos; Tsinopoulos, Ioannis T.; Dimitrakos, Stavros A.; Kruse, Friedrich; Welge-Luessen, Ulrich (Clinical and Experimental Ophthalmology, 2013)
To determine the time-dependent toxicity of Trypan blue at 0.06% concentration in cultured human trabecular meshwork cells.Human trabecular meshwork cells cultured in vitro were exposed to Trypan blue and acute toxicity was evaluated. Cells were exposed for 5, 30, 60 s and for 5, 15, 30, 60 min to a commercially available Trypan blue preparation (Vision Blue; DORC International Zuidland, The Netherlands). Morphology was observed by phase-contrast microscopy and cell viability was measured using Hoechst 33342 (Intergen; Purchase, NY, USA) and propidium iodide assays to determine the percentage of living and dead cells.Morphological changes occurred mainly after 5 min of exposure to Trypan blue. Viability was 96.0% ± 3.6%, 94.8% ± 3.5% and 92.5% ± 4.4% after 5, 30 and 60 s of exposure, respectively; a significant toxic effect of Trypan blue was observed after 5, 15, 30 and 60 min of exposure with a viability of 85.0% ± 3.7%, 77.0% ± 6.7%, 70.8% ± 5.9% and 68.3% ± 8.7%, respectively.Trypan blue is not toxic, in terms of cell viability, over an exposure time of up to 60 s; however, further exposure results in a gradual increase in damage of cultured human trabecular meshwork cells.
EVALuna2:21109